Automated detection and enumeration of fluorescently labelled bacteria with flow cytometry (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Rapid identification of specific microorganisms in their natural environments is of high importance when their cultivation is either impossible or cannot provide valid results. One of the tools available for such purposes is flow-FISH where classical microscopic identification of microorganisms is combined with an automated enumeration system. Despite the high potential of flow-FISH there are still many unsolved issues to introduce the method. The aim of this research was to determine potential quantification limits of a simple flow-FISH protocol to ensure specific and rapid automated identification of target cells.The results of the study showed that at optimal hybridization conditions (16 hours of hybridization, 15 minutes post-hybridization washing and 3 ng/µl probe concentration) it is possible to specifically determine all main proteobacteria groups and Grampositive bacteria and discriminate among β and γ proteobacteria. Detection of α-proteobacteria was not achieved in this study. Despite the promising application potential of flow-FISH, high attention must be made to extensive cell loss (up to 59%) during preparation of samples for the analyses.